Windows 8 on demand - Johnson, Steve, 1961- (On demand (Indianapolis, Ind.), 2013)
A comprehensive guide to using Microsoft Windows 8 that covers more than five hundred tasks, discussing getting started, managing files and folders, customization, exploring the Internet, working with pictures and media, creating movies, setting up accounts, backing up systems, and other related topics.